A secondary battery diaphragm coating slurry, composite diaphragm and preparation method
By using a combined coating of nanocellulose whiskers and PMMA particles on the lithium-ion battery separator, the problem of the membrane being easily melted and decomposed at high temperatures is solved, and a high safety, lightweight and low-cost separator is achieved, which improves the battery cycle capacity and safety performance.
Patent Information
- Application Number
- CN202211553012.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-05
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2042-12-05
AI Technical Summary
The lithium-ion battery separators are easily melted and decomposed at high temperatures, affecting the electrochemical performance of the battery. The existing ceramic coatings have high cost and limited heat resistance, which affects the safety and energy density of the battery.
Using a combined coating of nanocellulose whiskers and PMMA particles, the multi-dimensional interwoven network structure is formed on the surface of the polyolefin base film to improve the heat resistance and adhesion of the membrane, and reduce production by optimizing component proportions and process conditions. cost.
It realizes high safety, lightweight and low cost of lithium-ion battery separators, improves the battery's circulation capacity retention and safety performance, and improves adhesion and heat resistance.
Smart Images

Figure BDA0003981206520000091 
Figure BDA0003981206520000111
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of secondary batteries, and in particular relates to a secondary battery diaphragm coating slurry and a secondary battery composite diaphragm, and further discloses a preparation method thereof. Background Art
[0002] As a new type of energy storage device, lithium-ion batteries have the advantages of high energy density, abundant resources, low price and environmental friendliness, and have received widespread attention and application in many fields. With the development of lithium-ion batteries in power batteries, the safety of lithium-ion batteries has attracted more and more attention from scientific researchers. Studies have shown that since the electrolyte is an organic substance, there are great safety hazards in safety tests such as needle puncture, overcharging, dropping, immersion, and hot box.
[0003] As a porous and highly functional material, lithium battery separator is mainly used in traditional liquid lithium-ion batteries. It is an important component of liquid lithium-ion batteries. It not only transmits lithium ions, but also isolates the positive and negative electrodes to avoid contact and short circuit. The performance of lithium battery separator has a decisive influence on the interface structure of the entire battery system, and directly affects the capacity, cycle and safety performance of the battery. Therefore, the optimization of the separator also plays an important role in improving the comprehensive performance of the battery. However, due to the inherent non-polar surface and low melting temperature of the separator raw material PE / PP, polyolefin separators will melt and decompose at temperatures above 150°C, thereby affecting the electrochemical performance of the battery and limiting the application of such separators in high-performance lithium-ion batteries.
[0004] In order to improve the application performance of the diaphragm, the existing technology modifies the surface of the polyolefin diaphragm by coating nano-scale inorganic ceramic particles and PVDF on the surface of the base film, and improves the high temperature resistance of the diaphragm with the help of the ceramic coating, while the PVDF coating helps to improve the bonding force between the diaphragm and the pole piece, as well as the absorbency and affinity of the diaphragm to the electrolyte. However, although the ceramic coating can improve the heat resistance of the diaphragm to a certain extent, since the ceramic particles are connected by a binder, after the temperature exceeds 150°C, as the temperature further increases, the polyolefin will melt, and then the ceramic coating particles will be pulverized, affecting the stability of the ceramic coating and the application performance of the battery diaphragm. Although the heat resistance will be further improved by combining a more heat-resistant adhesive and inorganic ceramic particles with smaller particle size to increase the packing density, the inorganic ceramic particles with smaller particle size will have a serious impact on their water absorption due to their large specific surface area, and their high specific gravity will also affect the energy density of the battery. In addition, the limited adhesion and high cost of PVDF also limit the application of the product to a certain extent.
[0005] Therefore, developing a lithium-ion battery separator with good application performance, simple operation and low production cost has positive significance for the development of lithium-ion batteries. Summary of the invention
[0006] To this end, the technical problem to be solved by the present invention is to provide a secondary battery separator coating slurry, which has the performance advantages of high safety and light weight as well as the economic advantage of low production cost;
[0007] The second technical problem to be solved by the present invention is to provide a secondary battery composite separator, which not only has good heat resistance and adhesion, but also has the advantages of light weight and low cost;
[0008] The third technical problem to be solved by the present invention is to provide a method for preparing the above-mentioned secondary battery separator coating slurry and secondary battery composite separator.
[0009] In order to solve the above technical problems, the secondary battery separator coating slurry described in the present invention includes a solvent, and nanocellulose whiskers, PMMA particles, a binder, a thickener, a dispersant and a wetting agent dispersed in the solvent; wherein,
[0010] The diameter of the nanocellulose whiskers is 4-20 nm and the length is 100-500 nm;
[0011] The particle size D50 of the PMMA particles is 3-5 μm;
[0012] Preferably, the mass ratio of the nanocellulose whiskers to the PMMA is 2.5-7:1.
[0013] Specifically, the secondary battery separator coating slurry, the solvent includes water;
[0014] Preferably, the solid content Wt of the slurry is 0.25≤Wt%≤0.45.
[0015] Specifically, in the secondary battery separator coating slurry, the mass ratio of the binder to the total amount of the nanocellulose whiskers and PMMA particles is 4-7:100;
[0016] Preferably, the binder comprises a water-based adhesive;
[0017] Preferably, the adhesive comprises an acrylic adhesive and / or an acrylate adhesive;
[0018] Preferably, the binder includes polyethyl acrylate and / or polyethyl methacrylate.
[0019] Specifically, in the secondary battery separator coating slurry, the mass ratio of the thickener to the total amount of the nanocellulose whiskers and PMMA particles is 1.5-2:100;
[0020] Preferably, the thickener comprises sodium carboxymethyl cellulose.
[0021] Specifically, in the secondary battery separator coating slurry, the mass ratio of the dispersant to the total amount of the nanocellulose whiskers and PMMA particles is 1-2:100;
[0022] Preferably, the dispersant comprises an acrylate dispersant;
[0023] Preferably, the dispersant comprises sodium acrylate and / or ammonium acrylate.
[0024] Specifically, in the secondary battery separator coating slurry, the mass ratio of the wetting agent to the total amount of the coating slurry is 0.03-0.04:100;
[0025] Preferably, the wetting agent comprises a fatty alcohol wetting agent;
[0026] Preferably, the wetting agent comprises at least one of polyethanol, glycerol or propylene glycol.
[0027] The present invention also discloses a method for preparing the secondary battery separator coating slurry, comprising the steps of sequentially adding selected amounts of the dispersant, nanocellulose whiskers, PMMA particles, thickener, binder and wetting agent into the solvent for dispersion.
[0028] As an practicable manner, the method for preparing the secondary battery separator coating slurry comprises: first dispersing the dispersant and deionized water; adding the nanocellulose whiskers to the above aqueous solution and dispersing for 20-40 minutes; adding the PMMA particles (or prepared as a dispersion) to the above aqueous solution and dispersing for 20-40 minutes; adding the thickener, binder and wetting agent in sequence, and continuing stirring for 10-30 minutes to obtain the desired coating slurry.
[0029] The present invention also discloses a secondary battery composite separator, comprising a base film, wherein at least one surface of the base film is formed with a coating formed by curing the coating slurry;
[0030] Preferably, the base film comprises a polyethylene diaphragm;
[0031] Preferably, the coating has a thickness of 2-4 μm.
[0032] The present invention also discloses a method for preparing the secondary battery composite separator, comprising the steps of coating the coating slurry on at least one surface of the base film and performing a drying process;
[0033] Preferably, the conditions of the drying step include: drying temperature 60-75° C., and drying time 2-5 min.
[0034] Preferably, the coating step adopts a gravure transfer coating method;
[0035] Preferably, the coating step controls the coating thickness to be 2-4 μm.
[0036] The present invention also discloses a secondary battery, comprising a positive electrode sheet, a negative electrode sheet, and the secondary battery composite diaphragm;
[0037] Preferably, the secondary battery includes a lithium ion battery or a sodium ion battery.
[0038] The secondary battery diaphragm coating slurry of the present invention uses nanocellulose whisker materials with high wettability, high heat resistance and light weight and high adhesion and low-cost PMMA materials as raw materials. The slurry of the present invention, especially the nanocellulose whisker material CNC with a high aspect ratio, can form a multi-dimensional interwoven network structure, combined with its unique high thermal decomposition temperature (> 280°C), so that the heat resistance of the coating can reach 180°C, effectively improving the safety of the battery; and because the density of nanocellulose whiskers is light, it is reduced by 2 times compared with traditional alumina fillers, which can effectively reduce the surface density of the coated diaphragm. The slurry of the present invention uses PMMA polymethyl methacrylate, which contains a large number of polar groups such as ester groups on its specific surface. During the hot pressing process, it can not only form physical bonding, but also has a stronger force between molecules to make its bonding force higher than PVDF; in particular, the preferred PMMA particles are larger than the conventional PMMA particle size, and the contact area is larger after hot pressing. A small amount of PMMA bonding force in the diaphragm can reach the PVDF level, and the cost is lower than PVDF. The lithium-ion battery separator coating slurry of the present invention takes into account the advantages of nanofiber whisker materials and PMMA materials, effectively solves the problems of high specific gravity and high production cost of traditional coating slurry separators, and can achieve one-time pulping and coating, simplifying the operation process and having high industrial promotion value.
[0039] The secondary battery separator of the present invention is formed by coating a mixed coating of inorganic nanofiber whisker material and PMMA particles with high safety adhesion on the surface of a polyolefin base film to form a modified separator. The separator not only has good heat resistance and high adhesion, but also has low moisture content, light density and low cost. The secondary battery separator of the present invention has significantly reduced thermal shrinkage and surface density at 180°C, and greatly improved adhesion. The lithium ion battery prepared using the separator of the present invention has better cycle capacity retention rate and safety performance, which can improve the safety of the battery, improve adhesion, and also realize lightweight design of the battery cell. DETAILED DESCRIPTION
[0040] Example 1
[0041] In the coating slurry of this embodiment, the diameter of the nanocellulose whiskers is 12±2 nm, and the length is 200±20 nm; the particle size of the PMMA particles is 4±0.2 μm.
[0042] The coating slurry described in this embodiment is prepared according to the following component addition ratios:
[0043] The mass ratio of the nanocellulose whiskers to PMMA is 6:1;
[0044] The mass ratio of the sodium carboxymethyl cellulose to the total amount of the PMMA and the nanocellulose whiskers is 1.5:100;
[0045] The mass ratio of the effective component of the methyl acrylate aqueous adhesive to the total amount of the PMMA and the nanocellulose whiskers is 5:100;
[0046] The mass ratio of the sodium acrylate dispersant to the total amount of PMMA and nanocellulose whiskers is 1.5:100;
[0047] The mass ratio of the wetting agent to the total amount of the slurry is 0.035:100;
[0048] The amount of deionized water added is such that the solid content Wt in the slurry is 36 wt %.
[0049] The method for preparing the lithium-ion battery separator coating slurry described in this embodiment includes: first dispersing the dispersant and deionized water; adding the nanocellulose whiskers to the above aqueous solution and dispersing for 30 minutes; adding the PMMA particles to the above aqueous solution and dispersing for 30 minutes; adding the thickener, binder and wetting agent in sequence, and continuing to stir for 20 minutes to obtain the desired coating slurry.
[0050] The prepared coating slurry is coated on one side of a 9 μm thick PE base film by gravure transfer coating, the coating thickness is controlled to be 2 μm, and baked at 60-75° C. for 2-5 minutes to obtain the desired lithium-ion battery composite separator.
[0051] Example 2
[0052] In the coating slurry of this embodiment, the diameter of the nanocellulose whiskers is 12±2 nm, and the length is 200±20 nm; the particle size of the PMMA particles is 4±0.2 μm.
[0053] The coating slurry described in this embodiment is prepared according to the following component addition ratios:
[0054] The mass ratio of the nanocellulose whiskers to PMMA is 2.5:1;
[0055] The mass ratio of the sodium carboxymethyl cellulose to the total amount of the PMMA and the nanocellulose whiskers is 2:100;
[0056] The mass ratio of the effective component of the methyl acrylate aqueous adhesive to the total amount of the PMMA and the nanocellulose whiskers is 4:100;
[0057] The mass ratio of the sodium acrylate dispersant to the total amount of PMMA and nanocellulose whiskers is 2:100;
[0058] The mass ratio of the wetting agent to the total amount of the slurry is 0.03:100;
[0059] The deionized water is added in an amount such that the solid content Wt in the slurry is 25 wt %.
[0060] The configuration method of the lithium-ion battery separator coating slurry described in this embodiment is the same as that in Embodiment 1.
[0061] The prepared coating slurry is coated on one side of a 9 μm thick PE base film by gravure transfer coating, the coating thickness is controlled to be 2 μm, and baked at 60-75° C. for 2-5 minutes to obtain the desired lithium-ion battery composite separator.
[0062] Example 3
[0063] In the coating slurry of this embodiment, the diameter of the nanocellulose whiskers is 12±2 nm, and the length is 200±20 nm; the particle size of the PMMA particles is 4±0.2 μm.
[0064] The coating slurry described in this embodiment is prepared according to the following component addition ratios:
[0065] The mass ratio of the nanocellulose whiskers to PMMA is 7:1;
[0066] The mass ratio of the sodium carboxymethyl cellulose to the total amount of the PMMA and the nanocellulose whiskers is 1.8:100;
[0067] The mass ratio of the effective component of the methyl acrylate aqueous adhesive to the total amount of the PMMA and nanocellulose whiskers is 7:100;
[0068] The mass ratio of the sodium acrylate dispersant to the total amount of the PMMA and the nanocellulose whiskers is 1:100;
[0069] The mass ratio of the wetting agent to the total amount of the slurry is 0.04:100;
[0070] The deionized water is added in an amount such that the solid content Wt in the slurry is 45 wt %.
[0071] The configuration method of the lithium-ion battery separator coating slurry described in this embodiment is the same as that in Embodiment 1.
[0072] The prepared coating slurry is coated on one side of a 9 μm thick PE base film by gravure transfer coating, the coating thickness is controlled to be 2 μm, and baked at 60-75° C. for 2-5 minutes to obtain the desired lithium-ion battery composite separator.
[0073] Example 4
[0074] The raw material composition and proportion of the coating slurry described in this embodiment are the same as those in Example 1, with the only difference being that the diameter of the nanocellulose whiskers is 5±1 nm and the length is 80±20 nm; and the particle size of the PMMA particles is 3.2±0.2 μm.
[0075] Example 5
[0076] The raw material composition and proportion of the coating slurry described in this embodiment are the same as those in Example 1, with the only difference being that the diameter of the nanocellulose whiskers is 18±2 nm and the length is 480±20 nm; and the particle size of the PMMA particles is 4.8±0.2 μm.
[0077] Comparative Example 1
[0078] The raw material components and proportions of the coating slurry in this comparative example are the same as those in Example 1, except that an equal amount of aluminum oxide (D50 is 0.3-0.5 μm) is used to replace the nanocellulose whiskers, and an equal amount of PVDF is used to replace the PMMA particles.
[0079] The prepared coating slurry is coated on one side of a 9 μm thick PE base film by gravure transfer coating, the coating thickness is controlled to be 2 μm, and baked at 60-75° C. for 2-5 minutes to obtain the desired lithium-ion battery composite separator.
[0080] Comparative Example 2
[0081] The raw material components and proportions of the coating slurry in this comparative example are the same as those in Example 1, with the only difference being that the diameter of the nanocellulose whiskers is 25±2 nm and the length is 800±20 nm.
[0082] Comparative Example 3
[0083] The raw material components and proportions of the coating slurry in this comparative example are the same as those in Example 1, the only difference being that the particle size of the PMMA particles is 1±0.2 μm.
[0084] Comparative Example 4
[0085] The raw material components and proportions of the coating slurry in this comparative example are the same as those in Example 1, except that the diameter of the nanocellulose whiskers is 25±2 nm, the length is 800±20 nm, and the particle size of the PMMA particles is 1±0.2 μm.
[0086] Comparative Example 5
[0087] The raw material components and proportions of the coating slurry in this comparative example are the same as those in Example 1, the only difference being that the mass ratio of the nanocellulose whiskers to PMMA is 1.5:1.
[0088] Comparative Example 6
[0089] The raw material components and proportions of the coating slurry in this comparative example are the same as those in Example 1, the only difference being that the mass ratio of the nanocellulose whiskers to PMMA is 8:1.
[0090] Comparative Example 7
[0091] The coating slurry described in this comparative example was prepared according to the scheme described in Example 3 of Chinese Patent CN107256936A.
[0092] The prepared coating slurry is coated on one side of a 9 μm thick PE base film by gravure transfer coating, the coating thickness is controlled to be 2 μm, and baked at 60-75° C. for 2-5 minutes to obtain the desired lithium-ion battery composite separator.
[0093] Comparative Example 8
[0094] The coating slurry described in this comparative example was prepared according to the scheme described in Example 2 of Chinese Patent CN107256936A.
[0095] The prepared coating slurry is coated on one side of a 9 μm thick PE base film by gravure transfer coating, the coating thickness is controlled to be 2 μm, and baked at 60-75° C. for 2-5 minutes to obtain the desired lithium-ion battery composite separator.
[0096] Experimental example
[0097] 1. Composite diaphragm performance test
[0098] The performance of the lithium ion battery composite diaphragms prepared in the above Example 1 and Comparative Examples 1-8 were tested respectively, and the testing method was as follows:
[0099] (1) Thermal shrinkage: Use a steel ruler to measure the dimensional change of the diaphragm before and after heating to 180°C for 1 hour, and calculate the shrinkage, referring to GB / T36363-2018;
[0100] (2) Surface density test refers to GB / T36363-2018;
[0101] (3) Adhesion test: The coated surface of the diaphragm is placed in contact with the positive electrode plate, and the adhesion between the diaphragm and the electrode plate is tested after hot pressing under certain conditions.
[0102] The test results are shown in Table 1 below.
[0103] Table 1 Lithium-ion battery composite diaphragm performance test results
[0104]
[0105] It can be seen from the data in Table 1 above that the thickness of the lithium-ion battery composite diaphragm prepared under the slurry system provided in Examples 1-3 of the present invention is between 11-11.5 μm, the thermal shrinkage at 180°C is no more than 2.5%, the adhesion is higher than 5 N / m, and the moisture content is no more than 1000 ppm, indicating that the composite diaphragm provided by the present invention has the advantages of good heat resistance, adhesion and light density.
[0106] Compared with the diaphragm scheme in Example 1, the scheme in Comparative Example 1 shows that the mixed coating of nanocellulose whiskers and PMMA has a lighter surface density, better adhesion and heat resistance than the alumina PVDF coating; the scheme in Comparative Example 2 proves that the size of the nanofiber is too large, which will affect the viscosity of the slurry and increase the difficulty of the processing process. At the same time, the nanocellulose whiskers are more likely to absorb water, affecting the moisture content of the diaphragm; the scheme in Comparative Example 3 proves that the PMMA particle size is too low, which will affect the bonding performance and interface effect of the diaphragm; Comparative Example 4 proves that the nanofiber size is too large and the PMMA size is too small, which will affect the moisture and adhesion of the diaphragm; the scheme in Comparative Example 5 proves that the mass ratio of nanocellulose whiskers and PMMA is too low, and the low nanofiber content affects the heat resistance and surface density of the diaphragm; the PMMA content is too much, the adhesion is strong, but there is a disadvantage of pore blocking; the scheme in Comparative Example 6 proves that the mass ratio of nanocellulose whiskers and PMMA is too high, the nanocellulose whisker content is too high, the heat resistance is good but the moisture content of the diaphragm is high; the low PMMA content affects the adhesion of the diaphragm. In particular, compared with the solutions in Comparative Examples 7 and 8, the coating prepared by the present invention is lighter and thinner and has better bonding performance.
[0107] 2. Lithium-ion battery performance
[0108] The separators provided in the above-mentioned embodiment 1 and comparative examples 1-8 are respectively used to prepare lithium ion batteries, and the preparation methods are as follows:
[0109] The mass ratio of positive electrode slurry: lithium nickel cobalt manganese oxide: conductive agent SP: binder PVDF is 96.5:1.8:1.7;
[0110] The mass ratio of negative electrode slurry: graphite: conductive agent SP: binder SBR is 96.2:1.5:2.3;
[0111] Add each raw material in the positive and negative electrode slurry into the solvent according to the ratio, stir thoroughly to obtain a mixed slurry, then evenly coat the mixed slurry on the copper foil / aluminum foil, dry, roll and cut to obtain the required positive and negative electrode sheets;
[0112] The electrolyte selected was a conventional ternary system electrolyte on the market: the concentration of LiPF6 was 1.1 mol / L, and the mass ratio of the mixed solvent components was ethylene carbonate (EC): ethyl methyl carbonate (EMC): diethyl carbonate (DEC) = 3:5:2.
[0113] Preparation of lithium-ion batteries: Assemble the prepared negative electrode sheet, positive electrode sheet, separator and electrolyte, and then test the electrochemical performance.
[0114] The lithium ion batteries prepared by the diaphragms provided in the above Examples 1-3 and Comparative Examples 1-8 were subjected to electrochemical performance and safety tests respectively, and the test methods are as follows:
[0115] Cycle test: charge to 4.35V at 1C constant current, charge to 0.05C at constant voltage, discharge to 2.8V at 1C constant current, cycle number is 1000 times at 25℃ and 45℃, compare capacity retention rate;
[0116] Safety test: Put the assembled battery into a high temperature box, charge it to 4.35V at 1C constant current, charge it to 0.05C at constant voltage, and raise the temperature from room temperature to 150℃ / 180℃ at a rate of 5℃ / min. Keep the constant temperature for 30min, then stop heating, observe for 1h, and the test is over.
[0117] The test results are shown in Table 2 below.
[0118] Table 2 Lithium-ion battery application performance test results
[0119]
[0120] It can be seen from the data in Table 2 above that the capacity retention rate of the ion battery of the present invention after 1000 cycles at a current density of 1C at different temperatures is higher than that of the comparative example, and the safety performance is better.
[0121] Compared with the scheme in Example 1, the scheme in Comparative Example 1 shows that the mixed coating of nanocellulose whiskers and PMMA has better battery safety and cycle capacity retention rate than the mixed coating of alumina PVDF; the scheme in Comparative Example 2 proves that the nanofiber size is too large, and the nanocellulose whiskers are more likely to absorb water, affecting the safety of the battery; the scheme in Comparative Example 3 proves that the PMMA particle size is too small and the weak adhesion will affect the cycle performance of the battery; the scheme in Comparative Example 4 proves that the nanofiber size is too large and the PMMA size is too small will affect the safety and cycle performance of the battery; the scheme in Comparative Example 5 proves that the mass ratio of nanocellulose whiskers and PMMA is too low, and the low nanofiber content affects the safety of the battery; excessive PMMA content has the disadvantage of pore blocking and affects the cycle performance; the scheme in Comparative Example 6 proves that the mass ratio of nanocellulose whiskers and PMMA is too high, and the PMMA content is too low to affect the interface bonding effect and the cycle performance; in Comparative Examples 7 and 8, although the safety of the battery is close to the same level as that of Example 1, there is a certain gap in their interface bonding effect and cycle performance.
[0122] In summary, the secondary battery diaphragm coating slurry of the present invention uses nanocellulose whisker materials with a high aspect ratio and large-particle PMMA materials as raw materials, while taking into account the advantages of nanofiber whisker materials and PMMA materials, and has good adhesion and high safety performance. The secondary battery diaphragm coating slurry can effectively improve the heat resistance and adhesion of the secondary battery diaphragm, and has low moisture content, light density and low cost. The lithium-ion battery cycle capacity retention rate and safety performance prepared using the diaphragm of the present invention are better, which can improve the safety of the battery, improve adhesion, and also realize the lightweight design of the battery cell.
[0123] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.
Claims
1. A secondary battery separator coating slurry, characterized in that: The slurry is composed of a solvent, and nanocellulose whiskers, PMMA particles, a binder, a thickener, a dispersant and a wetting agent dispersed in the solvent; wherein, The solvent includes water; The diameter of the nanocellulose whiskers is 4-20 nm and the length is 100-500 nm; The particle size D50 of the PMMA particles is 3-5 μm; The mass ratio of the nanocellulose whiskers to the PMMA particles is 2.5-7:
1.
2. The secondary battery separator coating slurry according to claim 1, characterized in that: The solid content Wt of the slurry is 0.25≤Wt%≤0.
45.
3. The secondary battery separator coating slurry according to claim 1 or 2, characterized in that: The mass ratio of the binder to the total amount of the nanocellulose whiskers and PMMA particles is 4-7:
100.
4. The secondary battery separator coating slurry according to claim 3, characterized in that: The binder includes a water-based adhesive.
5. The secondary battery separator coating slurry according to claim 4, characterized in that: The adhesive includes an acrylic adhesive and / or an acrylate adhesive.
6. The secondary battery separator coating slurry according to claim 5, characterized in that: The binder includes polyethyl acrylate and / or polyethyl methacrylate.
7. The secondary battery separator coating slurry according to claim 1 or 2, characterized in that: The mass ratio of the thickener to the total amount of the nanocellulose whiskers and PMMA particles is 1.5-2:
100.
8. The secondary battery separator coating slurry according to claim 7, characterized in that: The thickener includes sodium carboxymethylcellulose.
9. The secondary battery separator coating slurry according to claim 1 or 2, characterized in that: The mass ratio of the dispersant to the total amount of the nano-cellulose whiskers and PMMA particles is 1-2:
100.
10. The secondary battery separator coating slurry according to claim 9, characterized in that: The dispersant includes an acrylate dispersant.
11. The secondary battery separator coating slurry according to claim 10, characterized in that: The dispersant includes sodium acrylate and / or ammonium acrylate.
12. The secondary battery separator coating slurry according to claim 1 or 2, characterized in that: The mass ratio of the wetting agent to the total amount of the coating slurry is 0.03-0.04:
100.
13. The secondary battery separator coating slurry according to claim 12, characterized in that: The wetting agent includes fatty alcohol wetting agents.
14. The secondary battery separator coating slurry according to claim 13, characterized in that: The wetting agent includes at least one of polyethanol, glycerol or propylene glycol.
15. A method for preparing the secondary battery separator coating slurry according to any one of claims 1 to 14, characterized in that: The method comprises the steps of sequentially adding selected amounts of the dispersant, nanocellulose whiskers, PMMA particles, a thickener, a binder and a wetting agent into the solvent for dispersion.
16. A secondary battery composite separator, characterized in that: The invention comprises a base film, at least one surface of which is formed with a coating formed by curing the coating slurry according to any one of claims 1 to 14.
17. The secondary battery composite separator according to claim 16, characterized in that: The base film includes a polyethylene separator.
18. The secondary battery composite separator according to claim 16 or 17, characterized in that: The thickness of the coating is 2-4 μm.
19. A method for preparing the secondary battery composite separator according to any one of claims 16 to 18, characterized in that: The method comprises the steps of coating the coating slurry on at least one surface of the base film and performing a drying process.
20. The method for preparing a secondary battery composite separator according to claim 19, characterized in that: The conditions of the drying step include: drying temperature 60-75° C., and drying for 2-5 minutes.
21. A secondary battery, characterized in that: It comprises a positive electrode sheet, a negative electrode sheet, and a secondary battery composite diaphragm as described in any one of claims 16 to 18.
22. The secondary battery according to claim 21, characterized in that: The secondary battery includes a lithium ion battery or a sodium ion battery.
Citation Information
Patent Citations
Polyvinylidene fluoride / cyanoethyl cellulose composite lithium ion battery diaphragm and preparation method thereof
CN107256936A
Preparation method and application of polyolefin / nanocrystal cellulose composite diaphragm
CN105185940A
Aqueous slurry for lithium battery coating membrane, lithium battery coating membrane and preparation methods of aqueous slurry and lithium battery coating membrane
CN107611320A
PMMA polymer coating diaphragm and preparation method thereof
CN111354907A
Coated diaphragm and preparation method thereof
CN114361706A